1992
DOI: 10.1007/bf00184545
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 in patients with complicated and uncomplicated myocardial infarction

Abstract: Endothelin-1 concentrations were measured in peripheral venous blood samples from 42 patients with acute myocardial infarction. In patients with ischemic or hemodynamic complications (n = 11), endothelin-1 concentrations were significantly higher already on admission (P = 0.008) and remained significantly higher until day 6 after admission compared to patients with uncomplicated infarctions (n = 31; P = 0.035). There were no close correlations between peak concentrations of endothelin-1 and creatine kinase or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
0
9
0
5
Order By: Relevance
“…Miyauchi et al (14) and others (12,16,(28)(29)(30) has been reported that plasma concentration of ET-1(1-21) in patients with acute myocardial infarction significantly rose after an attack and gradually decreased, and returned to the normal level in approximately two weeks. Furthermore, plasma concentrations of ET-1(1-21) rose after laparotomy and thoracotomy (31), coronary artery bypass grafting (32), and PTCA (33,34), and these values were gradually normalized after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Miyauchi et al (14) and others (12,16,(28)(29)(30) has been reported that plasma concentration of ET-1(1-21) in patients with acute myocardial infarction significantly rose after an attack and gradually decreased, and returned to the normal level in approximately two weeks. Furthermore, plasma concentrations of ET-1(1-21) rose after laparotomy and thoracotomy (31), coronary artery bypass grafting (32), and PTCA (33,34), and these values were gradually normalized after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that circulating ET-1 increases in the early hours after AMI [18,19], peaks within the first 24 h, and remains elevated after 48 h [18]. It has been reported that circulating ET-1 increases in the early hours after AMI [18,19], peaks within the first 24 h, and remains elevated after 48 h [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ET(B) receptors are upregulated in atherosclerotic human coronary arteries, although their functional role is unclear [66]. In patients with complicated acute myocardial infarction, ET-1 plasma levels are increased; the persistence of this increase depends on the severity of myocardial infarction [67,68]. In human atherosclerosis and experimental hypercholesterolemia, elevated plasma levels for ET hav been described [56].…”
Section: Coronary Artery Diseasementioning
confidence: 96%